2013
DOI: 10.1308/205016814809859563
|View full text |Cite
|
Sign up to set email alerts
|

Photoinitiators in Dentistry: A Review

Abstract: Polymerization of Resin Based Composites (RBCs) initiated by a light curing unit activating photoinitiators. Different RBCs require different light energy levels for proper curing. Manufacturers are now producing RBCs with more than one initiator and not all of these will be properly polymerised with blue LED lights. An added problem is that manufacturers do not always indicate the type of photoinitiators in their materials. This review discusses the importance of matching the spectral output of LCUs to the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 21 publications
3
78
0
4
Order By: Relevance
“…Camphorquinone (CQ) is the traditional initiator used in most RBCs and it is mostly activated by blue light peaking at 468 nm wavelength. Several new photoinitiators have been developed as an alternative to CQ, e.g., trimethylbenzoyldiphenylphosphine oxide (TPO, ranging from 375 to 410 nm) and 1-phenyl-1,2-propanedione (PPD, maximum wavelength ≈ 410 nm) (12,13). Some broad-spectrum LED units include additional LED emitters that produce light at these lower wavelengths, which are in the 'violet' range, to make these LCUs compatible with a wider range of…”
Section: Introductionmentioning
confidence: 99%
“…Camphorquinone (CQ) is the traditional initiator used in most RBCs and it is mostly activated by blue light peaking at 468 nm wavelength. Several new photoinitiators have been developed as an alternative to CQ, e.g., trimethylbenzoyldiphenylphosphine oxide (TPO, ranging from 375 to 410 nm) and 1-phenyl-1,2-propanedione (PPD, maximum wavelength ≈ 410 nm) (12,13). Some broad-spectrum LED units include additional LED emitters that produce light at these lower wavelengths, which are in the 'violet' range, to make these LCUs compatible with a wider range of…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of CQ in dental resins varies significantly. An analysis of seven visible-lightcurable dental composite resins revealed that the concentration of CQ in the resin phase was between 0.17 and 1.03 wt% (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…This moiety contains domain bond (almost double bond or epoxide) that is irreversibly changed by irradiation in the presence of PIS. Acrylates [63], methacrylates [13], and cyano-acrylates [46] are commonly used photosensitive moieties, that can be covalently crosslinked with the excitation of free radical generating PIs. Similarly, fumarate moiety which is commonly used for the formulation of different injectable/implantable biomaterials is covalently crosslinked upon exposure to photo-irradiation [64].…”
Section: Photo-responsive Precursorsmentioning
confidence: 99%
“…Several light sources have been practically explored for the photo-formulation including ultraviolet (UV) lamps, visible light lamps, plasma arc lamps, light emitted diode, titanium-sapphire laser, and gamma irradiator [16,19,20,46,53,93]. The main differences associated with those sources are the generated light wavelength, intensity and the associated amount of entropy loss (heat evolved) [53].…”
Section: Used Lightmentioning
confidence: 99%
See 1 more Smart Citation